Why Is Murat’s Achievement So Low? Causal Attributions and Implicit Attitudes Toward Ethnic Minority Students Predict Preservice Teachers’ Judgments About Achievement - Glock, Sabine; Shevchuk, Anna; Kleen, Hannah (Frontiers in Psychology, 2022)
In many educational systems, ethnic minority students score lower in their academic achievement and consequently, teachers develop low expectations regarding this student group. Relatedly, teachers’ implicit attitudes, explicit expectations and causal attributions also differ between ethnic minority and ethnic majority students—all in a disadvantageous way for ethnic minority students. However, what is not known so far, is how attitudes and causal attributions contribute together to teachers’ judgments. In the current study, we explored how implicit attitudes and causal attributions contribute to preservice teachers' judgments of the low educational success of an ethnic minority student. Results showed that both implicit attitudes and causal attributions predicted language proficiency and intelligence judgments. Negative implicit attitudes, assessed with the IRAP, and internal stable causal attributions led to lower judgments of language proficiency, whereas lower judgments of intelligence were predicted by positive implicit attitudes and higher judgments of intelligence by external stable attributions. Substantial differences in the prediction of judgments could be found between the IRAP and BIAT as measures of implicit attitudes